The action of insulin and dibutyryl cyclic AMP on the biosynthesis of polyunsaturated acids ofα-linolenic acid family in HTC cells - Tacconi de Alaniz, María Josefa (1976)
Incubation of HTC cells (7288 C) with 114C-α-linolenic acid in Swim's 77 medium during 24 hours converted the fatty acid to octadeca-6,9,12,15-tetraenoic acid, eicosa-11,14,17-trienoic acid, eicosa-8,11,14,17-tetraenoic acid, eicosa-5,11,14,17-tetraenoic acid, eicosa-5,8,11,14,17-pentaenoic acid and unsaturated acids of 22 carbons. The existence of two pathways was recognized: one initiated by a Δ6-desaturation and the other by an elongation ofα-linolenic acid. Incubation of the cells with insulin and dibutyryl cyclic AMP modified both pathways in different ways. HTC cells were sensitive to insulin which enhanced the de-saturating route increasing eicosapentaenoic acid synthesis and depressed the elongating route decreasing eicosatrienoic acid. In an opposite way, dibutyryl cyclic AMP decreased eicosapentaenoic acid synthesis and increased eicosatrienoic acid.